Prevotella histicola Protects From Arthritis by Expansion of Allobaculum and Augmenting Butyrate Production in Humanized Mice - Balakrishnan, Baskar; Luckey, David; Bodhke, Rahul; Chen, Jun; Marietta, Eric; Jeraldo, Patricio; Murray, Joseph; Taneja, Veena (Frontiers in Immunology, 2021)
Bacterial therapeutics are the emergent alternative in treating autoimmune diseases such as Rheumatoid Arthritis [RA]. P. histicola MCI 001 is one such therapeutic bacterium proven to treat autoimmune diseases such as RA and multiple sclerosis [MS] in animal models. The present study characterized P. histicola MCI 001 isolated from a human duodenal biopsy, and evaluated its impact on the gut microbial and metabolic profile in a longitudinal study using the collagen-induced arthritis model in HLA-DQ8.AEo transgenic mice. P. histicola MCI 001 though closely related to the type strain of P. histicola, DSM 19854, differed in utilizing glycerol. In culture, P. histicola MCI 001 produced vitamins such as biotin and folate, and was involved in digesting complex carbohydrates and production of acetate. Colonization study showed that duodenum was the predominant niche for the gavaged MCI 001. A longitudinal follow-up of gut microbial profile in arthritic mice treated with MCI 001 suggested that dysbiosis caused due to arthritis was partially restored to the profile of naïve mice after treatment. A taxon-level analysis suggested an expansion of intestinal genus Allobaculum in MCI001 treated arthritic mice. Eubiosis post treatment with P. histicola MCI 001 was also reflected in the production of short-chain fatty acids [SCFAs]. Present study suggests that the treatment with P. histicola MCI 001 leads to an expansion of Allobaculum by increasing the availability of simple carbohyrates and acetate. Restoration of microbial profile and metabolites like butyrate induce immune and gut homeostasis.